PENGARUH KUALITAS PRODUK KUALITAS LAYANAN DAN KEPUASAN TERHADAP LOYALITAS (Studi pada Pengguna IM3 di Wilayah Semarang) - Yudhi Ardiyanto, 08.05.51.0111; Marlien, Marlien (Students Journal of Economic and Management, 2012)
Based on research which has been done so we could know that quality product become better, and loyalty customer level toward the product become higher, and in the other hand, if the servicequality is better so the loyalty customer level toward the product also become higher, and if the product could satisfy to the user so the loyalty customer level toward the product also become higher. Samples in this study set a number of 100 respondents, using the technique of Purposive Sampling. And data collection techniques in the research is questioner. Product quality has a bigger influence toward the loyalty customer product. Almost the entire questioner toward quality product has been answered agreed by the respondents, until the IM3 product could show its IM3 operator performance that has function ability appropriate with main product which has been bought. Operator features IM3 cellular has another specialty appropriate with needand the trade on product operator IM3 cellular has been guaranteed.Key words : quality product, service quality, the user satisfaction, and loyalty customer.